Neoadjuvant chemoradiotherapy for rectal cancer: how important is tumour regression?. Issue 12 (3rd December 2015) - McCoy, Melanie J.; Hemmings, Chris; Hillery, Simon; Penter, Cheryl; Bulsara, Max K.; Zeps, Nik; Platell, Cameron F.
Abstract: Background: Pathological complete response following neoadjuvant chemoradiotherapy (CRT) for locally advanced rectal cancer is associated with reduced local recurrence and improved long‐term outcome. However, the prognostic value of a partial response, or of tumour regression in patients with metastatic disease, is less clear. Methods: We present a single‐centre cohort study of 205 patients with stage II–IV rectal cancer treated with surgery and neoadjuvant CRT between 2006 and 2013. Tumour regression was assessed using the Dworak system. Results: The probability of 3‐year recurrence‐free survival (RFS) was 95% for Dworak grade 4, 82% for grade 3, 64% for grade 2 and 53% for grade 1 ( P = 0.0005). In univariate regression analysis, Dworak grade was associated with RFS (hazard ratio (HR) 0.51, P < 0.0001; trend analysis) and cancer‐specific survival (HR 0.52, P = 0.002). In multivariate analysis, Dworak grade remained an independent predictor of RFS (HR 0.62, P = 0.012), along with clinical metastases stage, resection margin status, the presence or absence of extramural venous invasion and type of surgical procedure. Conclusions: Tumour regression grade after neoadjuvant CRT was an independent prognostic factor for RFS, highlighting the importance of the degree of local response to CRT.